Responsabilidad por violación de cuarentena: novedades de la legislación administrativa y penal - Sergii Starodubov; Viktoriia Vladyshevska; Maryna Pyzhova (Ius Humani. Jornal do direito, 2020)
Public legislation has long failed to meet such large-scale challenges as the SARS-CoV-2 pandemic. In emergencies, to protect the lives and health of the population, it is necessary to promptly make decisions on the legal regulation of public relations that have developed due to the spread of Covid-19. For this purpose, the state has created legal mechanisms that are designed to ensure compliance with the rule of law and which need the scientific-legal assessment. The objective of the work is to analyze the novelties of administrative and criminal legislation, which regulate the liability for violation of quarantine. The object of research is the norms of administrative and criminal law. The subject of the study is public relations that have developed as a result of the introduction of quarantine and which are governed by administrative and criminal law. To achieve this goal, the situation in foreign countries was firstly analyzed; general patterns were identified; alternative solutions were proposed, with a minimum restriction of human rights and freedoms. Then, the novelties of the national legislation were studied in more detail; additional specific problems were identified; and a more balanced legislative policy was proposed. As a result of the study, the current state of legal regulation in the areas of administrative and criminal law related to quarantine violations was analyzed; the liability for such offenses was characterized; some conclusions regarding the existing related problems were made and options for their solution were proposed, as well as propositions for modernization of legislation were made.